2016
DOI: 10.4028/www.scientific.net/amm.821.753
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trends in Annual Ground Snow Maxima for the Carpathian Region

Abstract: Abstract. The current structural design provisions are prevalently based on experience and on the assumption of stationary meteorological conditions. However, the observations of past decades and advanced climate models show that this assumption is debatable. Therefore, this paper examines the historical long-term trends in ground snow load maxima, and their effect on structural reliability. For this purpose, the Carpathian region is selected, and data from a joint research effort of nine countries of the regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…where snow accumulation is significant. A detailed analysis (Rózsás et al, 2016) focusing on the Carpathian region confirmed the Weibull distribution for mountains while arguing that a Fréchet (EVII) distribution provides the best fit for lowlands. The US experience advocates a lognormal distribution (ASCE 7-16, 2017) that has also been considered in some countries in Europe.…”
Section: Changes Of Load Patterns In Europe 1effects On Ground Snow L...mentioning
confidence: 81%
“…where snow accumulation is significant. A detailed analysis (Rózsás et al, 2016) focusing on the Carpathian region confirmed the Weibull distribution for mountains while arguing that a Fréchet (EVII) distribution provides the best fit for lowlands. The US experience advocates a lognormal distribution (ASCE 7-16, 2017) that has also been considered in some countries in Europe.…”
Section: Changes Of Load Patterns In Europe 1effects On Ground Snow L...mentioning
confidence: 81%
“…For details, we refer to Abidin et al (2012). We apply this test on the transformed data using Saeb (2018) and found that we cannot reject the null hypothesis (samples generated from the Gumbel model) at the 5 % significance level for almost all our selected models (98 %), justifying their good fit. As explained in Sect.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, according to the comparative study of Abidin et al (2012), the most powerful goodness-of-fit test for the Gumbel distribution is a combination of the Anderson-Darling test and the maximum likelihood estimator. We apply this test on the transformed data using Saeb (2018) and found that we cannot reject the null hypothesis (samples generated from the Gumbel model) at the 5 % significance level for almost all our selected models (98 %), justifying their good fit. We refer to Appendix B for more details.…”
Section: Model Selection Validation and Significancementioning
confidence: 93%
“…The probabilistic model of ground snow load is inferred from the snow water equivalent data of CarpatClim database (Szalai et al, 2013). The observations are available for 49 full winter seasons; the time trend of annual maxima is statistically insignificant (Rózsás et al, 2016) and is neglected. The basic statistical parameters of the annual (winter season) maxima are given in Table 2.…”
Section: Snow Actionmentioning
confidence: 99%